Perjanjian Jual Beli Virtual Property pada Game Online Ditinjau dari Hukum Perdata dan Perspektif Hukum Islam - 10040020120, Yoga Pratama; Arif Firmansyah (UNISBA Press, 2024)
Abstract. This research focuses on whether or not buying and selling virtual property in online games is legal according to Civil Law and Islamic Law. This research method is normative juridical. The results of this research are that the virtual property sale and purchase agreement in the online game Counter-Strike 2 fulfills all the requirements for the validity of an agreement under Article 1320 of the Civil Code which includes agreement between the parties, legal skills, a certain matter, and a lawful cause. Apart from that, this transaction is also in accordance with the provisions of the sale and purchase agreement regulated in Article 1457 of the Civil Code. The virtual property sale and purchase agreement in the online game Counter-Strike 2 from the perspective of Islamic law shows that this transaction is in accordance with the pillars and terms of sale and purchase regulated in Islam. Thus, the virtual property sale and purchase agreement in the Counter-Strike 2 game can be considered valid and in accordance with the principles of Islamic Law as long as all these conditions are fulfilled correctly by the seller and buyer. Abstrak. Penelitian ini berfokus pada sah tidaknya jual beli virtual property pada game online menurut Hukum Perdata dan Hukum Islam. Metode penelitian ini yuridis normatif. Hasil penelitian ini perjanjian jual beli virtual property pada game online Counter-Strike 2 memenuhi semua syarat sahnya perjanjian Pasal 1320 KUHPerdata yang meliputi kesepakatan para pihak, kecakapan hukum, suatu hal tertentu, dan suatu sebab yang halal. Selain itu transaksi ini juga sesuai dengan ketentuan perjanjian jual beli yang diatur dalam Pasal 1457 KUHPerdata. Perjanjian jual beli virtual property pada game online Counter-Strike 2 dari perspektif Hukum Islam menunjukkan bahwa transaksi ini sesuai dengan rukun dan syarat jual beli yang diatur dalam Islam. Meskipun barang yang diperjualbelikan adalah digital dan tidak fisik, transaksi ini memenuhi rukun jual beli menurut Jumhur Ulama.